Resveratrol, a potential radiation sensitizer for glioma stem cells both in vitro and in vivo - Long Wang; Linmei Long; Wenjuan Wang; Zhongqin Liang (Journal of Pharmacological Sciences, 2015)
Glioblastoma is a malignant human cancer that confers a dismal prognosis. Ionizing radiation (IR) is applied as the standard treatment for malignant gliomas. However, radiotherapy remains merely palliative because of the existence of glioma stem cells (GSCs), which are regarded as highly radioresistant “seed” cells. In this study, the effect and possible mechanisms of radiotherapy in combination with resveratrol (Res) were investigated in a radioresistant GSC line, SU-2. Our results showed that Res inhibited SU-2 proliferation and enhanced radiosensitivity as indicated by clonogenic survival assay. We also observed a decrease in the expression of neural stem cell marker CD133, which indicated that treatment with Res and IR induced SU-2 cell differentiation. In addition, the combination of Res with IR significantly increased autophagy and apoptosis levels in both in vitro cells and nude mouse model. Finally, Res significantly attenuated the repair of radiation-induced DNA damage. Taken together, the present study demonstrated that the significant radiosensitization ability of Res both in vitro and in vivo was attributed to its synergistic antitumor effects, including inhibition of self-renewal and stemness, induction of autophagy, promotion of apoptosis, and prevention of DNA repair. Therefore, Res may function as a radiation sensitizer for malignant glioma treatment.